Underdevelopment and Economic Theory of Growth: Case for Infant Industry Promotion - Zambakari, Christopher (Consilience, 2012)
The article reviews the literature on economic development, critiques neoliberal economic theories, and advances the theory of infant industry promotion as an alternative model for development in Africa. The essay argues that for developing countries to catch up to developed countries requires contextualizing development theory, applying selective economic policies to industries where productive capacities can be developed, and localizing the policy lessons to develop the productive abilities of local industries. The role of state in development and implementation of protective measures such as tariffs, import bans on key raw materials, and rebates on industrial inputs is discussed. To escape the Resource Curse, African states will have to develop an alternative source of employment, an industrial base, and strengthen the productive powers of infant industries if those industries are to survive fierce international competition. To be durable in the African context, economic policy must reflect local conditions, vary from one historical context to the next, use readily available resources, and adequately respond to local problems.